Laquinimod suppress antigen presentation in relapsing–remitting multiple sclerosis: In-vitro high-throughput gene expression study - Gurevich, M.; Gritzman, T.; Orbach, R.; Tuller, T.; Feldman, A.; Achiron, A. (Journal of neuroimmunology, 2010)
Laquinimod (LAQ) is a new immunomodulatory drug shown to be effective in the treatment of relapsing–remitting multiple sclerosis (RRMS); however, its molecular target pathways are not well recognized. In this study we characterized in-vitro the molecular effects of LAQ in peripheral blood mononuclear cells (PBMC) of healthy subjects and RRMS patients by gene expression microarrays. We demonstrated that LAQ induced suppression of genes related to antigen presentation and corresponding inflammatory pathways. These findings were demonstrated mainly via the NFkB pathway. Analysis of PBMC subpopulations identified activation of Th2 response in CD14+ and CD4+ cells and suppression of proliferation in CD8+ cells.